Double-layered laser induced graphene (LIG) porous composites with interlocked wave-shaped array for large linearity range and highly pressure-resolution sensor. (10th November 2022) - Chen, Lun; Hu, Bin; Gao, Xiang; Chang, Fu-lu; Yang, Han; He, Guang-jian; Cao, Xian-wu; Zou, Xin-liang; Yin, Xiao-chun
Abstract: There is an urgent need for developing flexible pressure sensors with ultra-high pressure-resolution and wide linear range to expand the application of wearable electronic devices. Here, a strategy was proposed for fabricating a LIG composite with wave-shaped array and multi-scale porous structure for wide-range and high-precision pressure detection. The synergism of the internal three-dimension porous structure and the inter-layer interlocked wave-shaped array endows the assembled double-layer LIG composite with numerous variable electrical conductive paths and easy deformation. Therefore, great improvements have been achieved in detection broad range and accuracy, exhibiting a large linearity range (0–100 kPa) and high pressure-resolution (millipascal-scale) over the full linearity range. These sensing properties make the double-layer LIG composites feasible for detecting subtle physiological signals and monitoring large human motions. Meanwhile, integrating the synthesis of graphene as active material and the design of flexible sensing structure by laser direct writing (LDW) technique provides an effective strategy for manufacturing high performance sensors with simple and low cost. Graphical abstract: Image 1 Highlights: LIG with porous structure and wave-shaped array structure was developed based on laser direct writing technology. The multi-scale microstructures allow piezoresistive materials to obtain numerous variable electrical conductive paths. The sensor shows large linearity range (0-100 kPa) and highly pressure-resolution. Multifunctional applications of the LIG composites have been demonstrated in health monitoring and thermotherapy.